2004
DOI: 10.1016/j.ypmed.2004.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of the potential impact of preventive therapy on the public health problem of tuberculosis in contemporary sub-Saharan Africa

Abstract: Background-To estimate the effect size of tuberculosis preventive therapy (PT) on the public health problem of tuberculosis in contemporary sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
5
0
5
Order By: Relevance
“…A number of trials and modeling analyses performed in sub-Saharan Africa have suggested that IPT may have limited population-level impact in that setting. 13,14,23,24 Our model suggests that the larger relative impact in moderate-burden settings such as urban Brazil may in part reflect differential risks of infection. In our model, the measured TB incidence rate among adults in Rio de Janeiro suggests an annual risk of TB infection (ARTI) of 0.8% – a risk that may be five times greater in hyperendemic settings in southern Africa.…”
Section: Discussionmentioning
confidence: 88%
“…A number of trials and modeling analyses performed in sub-Saharan Africa have suggested that IPT may have limited population-level impact in that setting. 13,14,23,24 Our model suggests that the larger relative impact in moderate-burden settings such as urban Brazil may in part reflect differential risks of infection. In our model, the measured TB incidence rate among adults in Rio de Janeiro suggests an annual risk of TB infection (ARTI) of 0.8% – a risk that may be five times greater in hyperendemic settings in southern Africa.…”
Section: Discussionmentioning
confidence: 88%
“…The uptake of IPT in this study was lower than the global estimate (32.5 %), although there was no clear reason for this underutilization or under prescription [ 19 ]. Possible reasons may be the health care professionals’ skepticism about potential drug resistance [ 24 ] and subsequent underestimation of potential public health impact [ 46 ], as well as lack of adequate means to exclude a pre-existing TB infection prior to treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…C'est un peu pessimiste même dans une zone où les habitants vivent dans une très grande pauvreté comme le bidonville sud-africain de notreétude. La mortalité est 0,0064 par an dans [31], 0,0081 par an dans [29] et 0,0167 par an dans [56].…”
Section: Paramètres Démographiquesunclassified
“…On a pris pour la mortalité des personnes séropositives µ 2 = 0,1 par an comme dans [10] pour avoir une survie moyenne de 10 ans. Cette mortalitéétait 0,13 par an dans [31] et dans [29] (d'après uneétude en Ouganda [53]). Schulzer et al [59] ont supposé une durée fixe de survie de dix ans.…”
Section: Paramètres Du Vih Pour Les Personnes Non Infectées Par M Tuunclassified
See 1 more Smart Citation